AL-JAM'IYATUL WASHLIYAH: CONTRIBUTIONS TO THE SOCIETY OF NORTH SUMATRA - Fakhrul Adabi; Sopian Ilyas (Program Pascasarjana UIN Sumatera Utara, 2021)
Al-Jam'iyatul Washliyah is a prestigious Islamic organization that wasestablished in North Sumatra, and has made significant contributions to thesociety and greatly influenced the lives of Muslims, especially in the region. Hence,Karel A. Steenbrink said that Al-Washliyah emerged as a reformist organizationin North Sumatra. In the education field, the contribution of this organization issubstantial, especially in improving education in North Sumatra in accordancewith the local people’s expectations and ideals of advancing the nation’s educationsystem, through the combination of traditional and modern education methods.Chalidjah Hasanuddin stated that Al-Washliyah had extraordinary influence dueto its rapid development, and had a very large contribution in spreading thesymbol of Islam to all corners of Indonesia, especially in the Batak Lands of NorthSumatra. This success is the result of Maktab Islamiah Tapanuli students’persistence; who were the pioneers of this organization